SOME REMARKS ON PHYTONYMS IN UZBEK FOLK-TALES - Hamid Xushmurodovich Bozorov (Scholar Express Journal, 2022)
This article discusses the use of phytonyms in Uzbek folk tales and linguistic and cultural features of the onamastic department of linguistics, which studies the world of plants. Also, the main characteristics of fruit names, cultural signs that have existed since ancient times form the basis of the article. At this point, it is noteworthy that our article focuses on the issues of perception of fruits in the linguistic landscape of a person, recorded in rare sources of the world and the Uzbek people.
Keywords: phytonym; culture; onomastics; Rabguzi